Causality between Inflation Rate and Stock Prices Index (Evidence from Damascus Securities Exchange) - Yaghi, Kinan Mostafa (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aims to examine the causal relationship between the inflation rate and the stock prices in Damascus Securities Exchange (DSE), for determining which is the dependent variable and the independent variable. Over the period of January 2011 to December 2017 using monthly data observations. The causal relationship between the two variables was tested using the Granger Causality Test, which helps to examine the nature of the causal relationship among time series, while vector autoregression-VAR model was used to excluding the effect of the self-correlation between the two variables. The empirical result concluded that the inflation rate and stock price data series are stationary and integrated of order one. Then we have applied Johansen procedure to test for the possibility of a co-integrating relationship. The result displays that there is a cointegrating relationship between stock prices and inflation rate. The Granger causality test also indicates that stock prices have a unidirectional causality on the inflation rate. That means stock prices Granger-cause inflation rate. يهدف البحث إلى دراسة العلاقة السببية بين معدل التضخم وأسعار الأسهم المتداولة في سوق دمشق للأوراق المالية، وذلك بهدف تحديد المتغّير التابع والمتغّير المستقل. ولدراسة هذه العلاقة تمّ استخدام بيانات شهرية لكل من السلاسل الزمنية لمتغّيرات البحث (معدل التضخم، مؤشّر سوق دمشق للأوراق المالية) ويغطي البحث فترة زمنية تصل إلى 7 سنوات من بداية العام 2011 وحتى نهاية العام 2017. تمّ اختبار العلاقة السببية بين متغّيريّ البحث باستخدام تحليل جرانجر للسببية Granger Causality Test والذي يساعد على فحص طبيعة العلاقة السببية بين السلاسل الزمنية. في حين تمّ استخدام نموذج الانحدار الذاتي (Vector autoregression- VAR) بهدف استبعاد أثر الارتباط الذاتي بين المتغّيريّن. وتوصّل البحث إلى أنّ السلاسل الزمنية لمتغّيرات البحث (معدل التضخم، مؤشّر السوق) مستقرة عبر الزمن عند الفرق الأول أي متكاملة من الدرجة الأولى. وإلى وجود علاقة سببية باتّجاه واحد، إذ هناك تأثير جوهري لمؤشّر السوق على معدل التضخم، في حين لا يوجد أي تأثير لمعدل التضخم على مؤشّر السوق. وبالتالي فإنّ مؤشّر السوق هو المتغّير المستقل ومعدل التضخم هو المتغّير التابع والعلاقة السببية هي باتّجاه واحد فقط.